Mengatasi Kesulitan Membaca Menggunakan Explosion Box Siswa Kelas III di SD Swasta Islam Nursyamsiani Desa Bintang Meriah Kecamatan Batang Kuis - Hamidah Sal’aty; Tri Indah Kusumawati; Safran Safran (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This journal discusses a study titled "Overcoming Reading Difficulties Using an Explosion Box for Class III Students at Nursyamsiani Islamic Private Elementary School, Bintang Festive Village, Batang Kuis Sub-district." The research aims to: (1) identify forms of reading difficulties among third-grade students; (2) explore the use of explosion boxes as a medium to address these difficulties; (3) identify challenges teachers face in using the media; and (4) describe efforts to overcome these challenges. This qualitative research involved the school principal and third-grade teacher as participants. Data were collected through observation, interviews, and data analysis techniques such as reduction, presentation, and verification. The findings show that students struggle with distinguishing similar letters (e.g., b and d, m and n, p and q), slow spelling, repeated letters or words, and difficulties with diphthongs and consonant blends. The explosion box proved helpful in addressing these challenges by providing engaging, interactive reading experiences. However, teachers encountered obstacles such as small image sizes, limited school facilities, and financial constraints in media production. To address these issues, teachers implemented strategies like rotating the explosion box among students, ensuring visibility for those in the back, and providing additional explanations for unclear material. verall, this study underscores the importance of creative teaching media in overcoming reading difficulties. It highlights the need for schools to support teachers with resources and training to enhance learning effectiveness and student engagement in the classroom.